Explaining the Sociological Factors Associated with the Children's School Participation in Elementary Level - Tolentino, Melanie P. (Animo Repository, 2017)
This paper identifies the factors such as demographic, economic, and sociological factors that influence the children’s school participation in elementary level. Highlight of this study is explaining the context of mother’s absence in a household as it influences the children’s school participation. This paper utilized both quantitative and qualitative techniques in the data collection and analysis. The data set from Annual Poverty Indicators Survey 2011 was analyzed using descriptive statistics, correlation, and regression analysis. Selected families with 6-11 years old children whose mothers are working abroad were also interviewed to provide an understanding of the relevance of social resource within families in the children’s school participation.